Features of microbiological diagnosis and choice of selective antibiotic therapy in patients with acute cholecystitis - Salmanov, A. G.; Mamchich, V. I.; Potochilova, V. V.; Rudneva, E. L.; Chaika, M. A. (Journal of Education, Health and Sport, 2019)
The objective: to improve the results of destructive forms of acute cholecystitis (AC) surgery by the development of antibiotic therapy algorithm and taking into account the severity of the disease according to Tokyo guidelines (2013). Materials and methods: 266 patients having been operated on for AC made up a treatment group and 203 patients - the control one. In 234 treatment group patients microflora’s bacteriological study was carried out and its selective sensitivity to antibiotics was determined. Results and discussion. The AC treatment group patients (n=266) were arranged according to Tokyo guidelines (2013) into 3 grades. Mild course (grade I) consisted of 29 patients (11%), microbiological studies were not conducted. Antibiotic prophylaxis with beta-lactam antibiotics was used. At moderately severe AC (grade II, n = 200, 75%) escalation antibiotic therapy was carried out. At severe disease (grade III, n = 37, 14%) de-escalation antibiotic therapy was performed. Bacteriological studies were conducted in 237 patients with destructive forms of AC, at that 531 microflora isolates were cultured. Intestinal group microorganisms were the most frequently cultured. Beta-lactam antibiotics’ sensitivity was prevailing and constituted 83.3%. The number of suppurations in the treatment group decreased from 9.8% to 4.3%, and mortality rate decreased from 1.48% to 0.75% (p<0.05) as contracted with control group where empirical antibiotic therapy was used. Conclusions. 1. Intestinal group microflora prevailed in destructive forms of AC. 2. In mild course of cholecystitis antibiotic prophylaxis is consider to be method of choice, in moderately severe disease – escalating therapy, and in severe cases – de-escalating antibiotic therapy should be used, as that beta-lactam antibiotics had the highest selective sensitivity (83.3%). 3. AC is local intra-abdominal infection, where evidence-based antibiotic therapy has reduced postoperative complications to 4.3%, and mortality rate - to 0.75%.